2005
DOI: 10.1128/mcb.25.17.7770-7779.2005
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Aquaporin-11 Produces Polycystic Kidneys following Vacuolization of the Proximal Tubule

Abstract: Aquaporin-11 (AQP11) has been identified with unusual pore-forming NPA (asparagine-proline-alanine) boxes, but its function is unknown. We investigated its potential contribution to the kidney. Immunohistochemistry revealed that AQP11 was localized intracellularly in the proximal tubule. When AQP11 was transfected in CHO-K1 cells, it was localized in intracellular organelles. AQP11-null mice were generated; these mice exhibited vacuolization and cyst formation of the proximal tubule. AQP11-null mice were born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
269
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(285 citation statements)
references
References 25 publications
(41 reference statements)
15
269
0
1
Order By: Relevance
“…npg [68], rat [67]). Most recently, localization of the protein has been restricted to the late stages of spermiogenesis, first appearing in step 16 of spermatid elongation in the caudal cytoplasm and gradually becoming concentrated in vesicular organelles [69].…”
Section: Aqp11-12mentioning
confidence: 99%
See 1 more Smart Citation
“…npg [68], rat [67]). Most recently, localization of the protein has been restricted to the late stages of spermiogenesis, first appearing in step 16 of spermatid elongation in the caudal cytoplasm and gradually becoming concentrated in vesicular organelles [69].…”
Section: Aqp11-12mentioning
confidence: 99%
“…Although the water permeability of AQP11 was in doubt when it was initially expressed in plasma membranes [67], a high water conductance has since been shown when it is expressed in liposomes [81]. In Aqp11 knockout mice [68], cells in the proximal renal tubule show vacuolation, which results in the formation of polycystic kidney. Unfortunately, as the animals die of renal failure before puberty, this transgenic model sheds no light on the role of AQP11 in the testis, in which the protein is first expressed when the first wave of spermatogenesis is near completion [69].…”
Section: Aqp11mentioning
confidence: 99%
“…However, the functions of NPA motifs in AQP biogenesis remain largely unknown. Few AQP members with variations in NPA motifs such as AQP11 and AQP12 do not express in the plasma membrane (11,12), suggesting an important role of NPA motifs in AQP plasma membrane targeting.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for the association of AQP11 deficiency with renal cystogenesis remain unknown, though their elucidation might offer new insights on how and why renal cysts form in polycystic kidney disease. We found that primary cultures of proximal tubule cells from neonatal kidneys of AQP11 null mice manifest a mild defect in endosomal acidification (34). However, it is unclear whether defective endosomal acidification is involved in cyst pathogenesis or constitutes an epiphenomenon.…”
Section: Aqp11 and Renal Cystic Diseasementioning
confidence: 87%
“…Whether AQP11 functions as a water channel has been debated, though a recent report showed a small increase in water permeability in liposomes reconstituted with recombinant AQP11 (33). In kidney, AQP11 appears to be expressed in intracellular vesicles in proximal tubule (34), though available antibodies are limited in their specificity. AQP11 null mice manifest an interesting phenotype of vacuolization and cyst formation in proximal tubule, similar in some respects to polycystic kidney disease.…”
Section: Aqp11 and Renal Cystic Diseasementioning
confidence: 99%